Whitening dentifrice and tooth surface discoloration—a systematic review and meta‐analysis. Issue 1 (2nd June 2017) - Soeteman, GD; Valkenburg, C; Van der Weijden, GA; Van Loveren, C; Bakker, EWP; Slot, DE
Abstract: Objective: The aim of this systematic review was to assess the effect of a whitening dentifrice (WDF) relative to a regular dentifrice (RDF) on the reduction of natural extrinsic tooth surface discoloration (ETD). Materials and methods: The MEDLINE‐PubMed, Cochrane‐CENTRAL and EBSCO‐Dentistry and Oral Sciences databases were searched, up to April 2017. The inclusion criteria were as follows:(randomized)controlled clinical trials, healthy subjects ≥18 years of age, studies comparing WDF with RDF, a follow‐up period of at least 6 weeks and studies scoring ETD as the stain area/extent, stain intensity or a composite score. Studies using an induced staining model were excluded. Results: Independent screening of 851 unique papers resulted in 21 eligible publications, which included 32 comparisons. The descriptive analysis illustrated that the majority of comparisons showed a significant effect on ETD, in favour of WDF over RDF. The meta‐analysis substantiated this observation and revealed that the difference of means (diffM) comparing WDF and RDF was a reduction for stain area of −0.44 [(95% CI: −0.55; −0.339) ( P <.00001)] according to the original Lobene Stain Index; this result is in favour of the WDF. For the modified Lobene Stain Index, the diffM was −0.41 [(95% CI: −0.71; −0.10) ( P =.009)]. For overall stain intensity, the diffM was −0.35 [(95% CI: −0.44; −0.25) ( P <.00001)], and the composite score was −0.39 [(95% CI: −0.57; −0.21) ( P <.0001)] and −0.54 [(95% CI: −0.66; −0.43) ( P <.00001)]. Subgroup analysis differentiating between products that contained added chemical antidiscoloration agents showed a similar pattern. Conclusion: In this review, nearly all dentifrices that are specifically formulated for tooth whitening were shown to have a beneficial effect in reducing ETD, irrespective of whether or not a chemical discoloration agent was added.